ECONOMIC GROWTH SLOWDOWN AND PRODUCTION DECLINE IN THE EU - Tulkinova Aziza; Valieva Vazira (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract. The author considers the problems of EU economic growth in the period before the coronavirus pandemic, as well as during the economic crisis of 2020 and the subsequent gradual recovery of economic activity. The decline in economic growth in 2017-2019 was due to many long-term reasons, the main ones being the slow technological renewal of the production base and the reduction of the trade surplus due to the loss of advantages in competition with producers in Southeast Asia. The mechanisms of the impact of the pandemic on the EU production volume, caused by the decline in the aggregate demand and supply of goods and services, are analyzed. The role of EU economic policy as a tool to support the livelihood of the population and protect companies from bankruptcy is explored. The leading factor of economic recovery to pre-crisis levels is not economic policy measures, but overcoming the pandemic. It is predicted that the growth of the region's economy after its recovery will be slower due to the reasons that were formed even before the pandemic. In particular, it is the EU's policy to increasingly use "clean" energies and technologies that do not pollute the human environment, but force companies to increase production costs.